2007
DOI: 10.1109/tdmr.2007.897528
|View full text |Cite
|
Sign up to set email alerts
|

$I_{D}$– $V_{\rm GS}$-Based Tools to Profile Charge Distributions on NROM Memory Devices

Abstract: NROM memory cells are proposed as promising nonvolatile memories. Even though these devices should have a better endurance than their floating-gate counterparts, issues have risen due to the presence of both electrons and holes, for the control of their relative position and spread in the charge-trapping material. Thus, a deep knowledge of charge distribution features is crucial for program/erase bias optimization, reliability predictions, and future scaling. In this paper, we will introduce and discuss two to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A morphous silicon nitride films have attracted considerable attention as a promising solution for charge trapping layers in high-density nonvolatile semiconductor memories. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] In nitride-based charge trapping memories, electron and hole trapping processes induced by defect centers distributed in silicon nitride films are applied to data storage. This application requires an understanding of the nature of the defect centers.…”
mentioning
confidence: 99%
“…A morphous silicon nitride films have attracted considerable attention as a promising solution for charge trapping layers in high-density nonvolatile semiconductor memories. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] In nitride-based charge trapping memories, electron and hole trapping processes induced by defect centers distributed in silicon nitride films are applied to data storage. This application requires an understanding of the nature of the defect centers.…”
mentioning
confidence: 99%
“…Conventionally, many studies have been done for the charge distribution in SiN layer during programming in n-channel silicon-oxide-nitride-oxide-silicon (SONOS) devices, [1][2][3][4] using several methods, [5][6][7][8][9][10][11][12] such as comparison between sub-threshold and gate induced drain leakage (GIDL) characteristics, 1,6,7) studying V t difference between forward and reverse read. 4,11,12) These studies have revealed that injected charges were locally concentrated near to drain side until SiN trapped states are fully occupied by trapped charge.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous silicon nitride (Si 3 N 4 ) films have received considerable attention as charge tapping dielectric layers in silicon-oxide-nitride-oxide-silicon (SONOS) nonvolatile memory (NVM) devices. [1][2][3][4][5][6][7][8] In order to achieve excellent memory characteristics and reliability in SONOS type devices, it is important to understand the charge transport mechanisms involved and the role of point defects in silicon nitride films. Several authors have reported that charge transport in thick silicon nitride films at high fields and high temperatures can be attributed to Poole-Frenkel (PF) emission.…”
Section: Introductionmentioning
confidence: 99%